2001
DOI: 10.1074/jbc.m010967200
|View full text |Cite
|
Sign up to set email alerts
|

Programming the Transcriptional State of Replicating Methylated DNA

Abstract: CpG methylation is maintained in daughter chromatids by the action of DNA methyltransferase at the replication fork. An opportunity exists for transcription factors at replication forks to bind their cognate sequences and thereby prevent remethylation by DNA methyltransferase. To test this hypothesis, we injected a linearized, methylated, and partially single-stranded reporter plasmid into the nuclei of Xenopus oocytes and followed changes in the transcriptional activity after DNA replication. We find that dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This result implies that demethylation maybe a necessary step for reactivation of methylated p16 by p16ATFs. As transient p16ATF transfection alone does not lead to demethylation of p16 CpG islands, the process of stable p16ATF transfection inducing p16 demethylation may be a passive demethylation through inhibition of remethylation of the daughter DNA strands by DNMT1 at the replication forks, as observed in Xenopus oocytes by others (Matsuo et al, 1998;Stü nkel et al, 2001). The decreased binding of DNMT1 to p16 CpG island in the p16ATF transfected H1299 cells supports this hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…This result implies that demethylation maybe a necessary step for reactivation of methylated p16 by p16ATFs. As transient p16ATF transfection alone does not lead to demethylation of p16 CpG islands, the process of stable p16ATF transfection inducing p16 demethylation may be a passive demethylation through inhibition of remethylation of the daughter DNA strands by DNMT1 at the replication forks, as observed in Xenopus oocytes by others (Matsuo et al, 1998;Stü nkel et al, 2001). The decreased binding of DNMT1 to p16 CpG island in the p16ATF transfected H1299 cells supports this hypothesis.…”
Section: Discussionsupporting
confidence: 69%
“…This model has recently gained experimental support (33). However, more recent data have shown that passive demethylation is not simply dependent on the presence of DNA binding transcriptional activators (34). Yet still, other experiments have demonstrated site-and cell-specific active demethylation in transient transfection assays (35), suggesting the presence of site-and cell-specific demethylation machinery (36).…”
Section: Discussionmentioning
confidence: 97%